2013
DOI: 10.1002/jbm.b.32916
|View full text |Cite
|
Sign up to set email alerts
|

Application of a rotating bioreactor consisting of low‐cost and ready‐to‐use medical disposables for in vitro evaluation of the endothelialization efficiency of small‐caliber vascular prostheses

Abstract: The incomplete endothelialization of especially small-caliber vascular prostheses after implantation in patients is a major disadvantage in cardiovascular interventions. The lack of an endothelium leads to the occurrence of thrombosis at the luminal surface of artificial vascular prostheses. Thus, the development of new graft materials and coatings for induction of complete endothelialization on the implant surfaces is a promising approach to improve hemocompatibility and maintain long-term graft patency. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…BJ human foreskin fibroblasts (Stemgent, Cambridge, USA) were cultivated in DMEM with high glucose containing 10% FBS, 2 mM L-glutamine, 1% penicillin/streptomycin, and 30 mM HEPES (Life Technologies, Darmstadt, Germany). Human endothelial cells (ECs) were isolated as described previously [12] and cultivated in flasks precoated with 0.1% gelatin in Vasculife® EnGS EC culture medium (CellSystems, Troisdorf, Germany) containing VascuLife EnGS LifeFactors Kit, 50 mg/ml gentamicin, and 0.05 mg/ml amphotericin B (PAA Laboratories). Cells were kept at 37°C with 5% CO 2 and media was changed every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…BJ human foreskin fibroblasts (Stemgent, Cambridge, USA) were cultivated in DMEM with high glucose containing 10% FBS, 2 mM L-glutamine, 1% penicillin/streptomycin, and 30 mM HEPES (Life Technologies, Darmstadt, Germany). Human endothelial cells (ECs) were isolated as described previously [12] and cultivated in flasks precoated with 0.1% gelatin in Vasculife® EnGS EC culture medium (CellSystems, Troisdorf, Germany) containing VascuLife EnGS LifeFactors Kit, 50 mg/ml gentamicin, and 0.05 mg/ml amphotericin B (PAA Laboratories). Cells were kept at 37°C with 5% CO 2 and media was changed every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of primary human ECs from residual saphenous vein biopsies was performed as previously described and approved by the ethics committee of the University of Tuebingen, Tuebingen, Germany [ 17 ]. One day prior to the transfection, HEK293 cells and human ECs were seeded with a density of 150.000 cells per well onto a 12-well plate (Corning Costar, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The smooth muscle cells were cultured on the exterior of a decellularized matrix, while the endothelial cells were cultured on the lumen. Avci-Adali et al 86 discussed a rotating bioreactor based on ready-touse medical disposables to reendothelialize a vascular conduit. Their results demonstrated that expanded polytetrafluoroethylene (ePTFE) grafts with albumin and heparin coatings produced the most extensive endothelial cell adhesion and spreading.…”
Section: Bioreactor Designsmentioning
confidence: 99%